Poor writing skills in 1st and 2nd baccalaureate of María Auxiliadora High School and the e-portfolio to improve writing skills. - Andrade Ramos, Jorge Luis (2016)
This research study aims to analyze and offer a solution in a problematic area of English as a Foreign Language, which is writing composition. This project has as an objective the development of a technological tool (e-portfolio) to make students improve their writing skills through the proposal of a technological and collaborative methodology. An action research methodology was used to conduct this study since its process matched with the features of the present work. The participants of this study were students from María Auxiliadora high school from 1st and 2nd baccalaureate. To demonstrate the deficit of writing skills that the participants had, 56 writing sample papers were collected and analyzed by the researcher. This data was classified and quantified to show the different types of errors that the participants presented. In addition, statistics graphs were used to show the frequency of each of the errors found. The study revealed that the most common errors were related to grammar and punctuation. Based on the need to improve students’ writing skills, the e-portfolio arises as a solution to make students get better at writing. The proposed strategy consists on grouping students to work collaboratively under the basis of a process writing methodology aided with peer correction on each other’s documents (google docs). The documents are going to be developed by students individually. After students have written their first draft, they have to peer correct the two other documents of their peers using correction symbols proposed by the teacher at the beginning of the scholastic year. In this study, it is also established the role of the teacher as an audience, monitor, resource, evaluator, editor and examiner. In the methodology it is also considered a plan to assess students’ online performance.